Evolution des savanes a Vetiveria nigritiana et a Eragrostis barteri des plaines d'inondation du fleuve Niger (Mali central) - Diarra, L. (1988)
Discusses changes in the floristic composition and biomass production of eragrostis and vetiveria grasslands due to the rainfall and flood deficits during 1980-86 in the Niger floodplain in central Mali.